Speak Global, Sell Local? Digital Linguistic Landscape of Local Small Businesses in the Social Media - Enikő Biró (Acta Universitatis Sapientiae: Philologica)
This paper focuses on the online presence of languages and linguistic patterns of local small businesses in a bilingual, HungarianRomanian ethnic community in Romania. By capturing linguistic diversity and creativity via netnographic research, patterns of linguistic landscape elements in the social media, such as marketing strategy of local small businesses, can be analysed. The findings suggest that despite the need to advertise by using the state language, Romanian, in order to maximize the target audience, the concentration of Hungarian landscape elements is the highest. Businesses construct their linguistic identity by their language choices and practices, aligned with the collective linguistic identity of a bilingual community and the need for a global representation, in order to secure a place in the local market.